Photovoltaic performance of mixed cation K0.005MA0.995PbI3‐based perovskite solar module. Issue 2 (31st October 2022) - Singh, Harpreet; Dhakla, Shweta; Deendyal, Parvesh K.; Kumar, Anand; Kumar, Sarvesh; Kashyap, Manish K.
Abstract: Hybrid halide perovskites (HHPs) are attracting large attention due to their excellent photovoltaic characteristics. MAPbI3 (MA = CH3 NH3 ) based solar cells are widely studied both on experimental and theoretical fronts. Alkali metal ion doping in the absorbing layer material (MAPbI3 ) of HHP solar cells is helpful for enhancing the photovoltaic performance and stability of the complete solar module. In present work, a complete perovskite solar module with K‐doped MAPbI3 absorbing layer has been simulated numerically. The effect of various parameters such as thickness, defect density, series, and shunt resistances on device performance has been studied. After optimizing these parameters, a device with the maximum possible efficiency (20.69%) has been reported. The reproducibility of solar cells before and after optimization has also been compared with respect to the variation in carrier mobilities in absorber layer material. Higher reproducibility of the optimized device has been obtained as compared to the pristine device. This present work contains adequate information to run an experimental trial for designing solar module containing K‐doped MAPbI3 absorbing layer. Abstract : Efficient and reproducible K‐doped MAPbI3 ‐based hybrid halide perovskite solar module.